Analysis Of Changes in Earnings Per Share as A Result of Increased Inflation Through Changes in Interest Rate in The Property and Real Estate Industry - *, Sumaryoto; Nurfarkhana, Anna; Anita, Tri (Accounting Department,, 2022)
Purpose — This research aims to determine, prove and test several effects. These influences are an increase in inflation on EPS (earnings per share), an increase in inflation on the SBI interest rate (Bank Indonesia Certificate), the effect of the SBI interest rate on EPS in property and real estate companies, and EPS changes as a result of the indirect effect of inflation through SBI interest rates on property and real estate companies. Design/methodology/approach — This study uses a causal associative approach with a purposive sampling method based on several predetermined criteria. The sample used in this study amounted to 23 companies. The software used to analyze the data in this study is Eviews version 9.0.Findings — The results of this study indicate that the inflation rate has a positive and significant effect on EPS in property and real estate companies listed on the IDX; meanwhile, SBI has a positive but not significant impact on EPS. The results of this study indicate that the inflation rate has a positive and significant effect on EPS in property and real estate companies listed on the IDX. In contrast, SBI has a positive but not significant impact on EPS. Practical implications — This research uses panel data regression analysis Originality/value — This study aims to empirically test the effect of inflation on SBI and its impact on EPS. This research was conducted in the property and real estate industry. Originality/value — Bank Indonesia Certificate; BI Interest Rate; Earnings per Share; Inflation Paper type — Research paper